Evaluation of the Th17 pathway in psoriasis and geographic tongue, - Bruna Lavinas Sayed Picciani; Tábata Alves Domingos; Thays Teixeira-Souza; Anna Karoline Fausto-Silva; Eliane Pedra Dias; Sueli Carneiro (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background: Psoriasis is a skin-articular disease with unclear etiopathogenesis. It has been suggested that the disease is immune-mediated by T-lymphocytes, predominantly Th17 cells. Similar to psoriasis, geographic tongue is an inflammatory disease with participation of Th17 cells and direct correlation with psoriasis. Objective: To investigate and compare the inflammatory responses and the Th17 pathway in psoriasis and geographic tongue. Methods: This was a cross-sectional study with 46 participants that were categorized into three groups: (A) patients with psoriasis vulgaris; (B) patients with geographic tongue and psoriasis; (C) patients with geographic tongue without psoriasis. All patients underwent physical examination, and a skin and oral biopsy for histopathological examination and immunohistochemical analysis with anti-IL6, anti-IL17, and anti-IL23 antibodies. Results: Histological analysis of all lesions showed mononuclear inflammatory infiltrate. However, moderate intensity was prevalent for the patients with geographic tongue and psoriasis and geographic tongue groups. Immunopositivity for the antibodies anti-IL6, anti-IL17, and anti-IL23 revealed cytoplasmic staining, mainly basal and parabasal, in both psoriasis and geographic tongue. Regarding IL-6, in patients with geographic tongue and psoriasis cases the staining was stronger than in patients with geographic tongue without psoriasis cases. IL-17 evidenced more pronounced and extensive staining when compared to the other analyzed interleukins. IL-23 presented similar immunopositivity for both geographic tongue and psoriasis, demonstrating that the neutrophils recruited into the epithelium were stained. Study limitation: This study was limited by the number of cases. Conclusion: The inflammatory process and immunostaining of IL-6, IL-17, and IL-23 were similar in geographic tongue and psoriasis, suggesting the existence of a type of geographic tongue that represents an oral manifestation of psoriasis.